ANALISIS NILAI TAMBAH KELAPA DI KECAMATAN PATILANGGIO KABUPATEN POHUWATO PROVINSI GORONTALO - Darmiati Dahar; Maharani maharani (Jurnal Sosial Ekonomi Pertanian (J-SEP), 2018)
One of the coconut producing areas in Gorontalo Province is Pohuwato District. Subdistrict Patilanggio is one of subdistrict in Pohuwato District that has a high enough production. Coconut plants are still be the main plant in this area. The purpose of this research is to know coconut productivity and value added obtained by farmers (from the processing of coconuts into copra). Data analysis used is analysis of productivity calculation and value added analysis of coconut with hayami method. The study was conducted in Patilanggio Subdistrict by selecting 3 (three) villages with the most farmers, namely: Manawa Village, Suka Makmur Village, and Dulomo Village. The results obtained, namely: 1) Productivity of coconut in District Patilanggio based on results if data obtained 1.7 tons / ha. 2). The added value obtained from processing coconut into copra is Rp. 1,547,46 / kg with added value ratio obtained for 55,57%. This means if the value of the product by 1 unit increases the added value obtained at 0.5557 units. An added value ratio of more than 50% is said to be high. It means that the processing of coconut into copra has high added value.